Generation of cytocompatible superhydrophobic Zr–Cu–Ag metallic glass coatings with antifouling properties for medical textiles. (September 2021) - Sharifikolouei, Elham; Najmi, Ziba; Cochis, Andrea; Scalia, Alessandro Calogero; Aliabadi, Maryam; Perero, Sergio; Rimondini, Lia
Abstract: Zirconium–Copper-based metallic glass thin films represent promising coatings in the biomedical sector for their combination of antibacterial property and wear resistance. However, finding a Zr–Cu metallic glass composition with desirable cytocompatibility and antibacterial property is extremely challenging. In this work, we have created a cytocompatible and (super-)hydrophobic Zr–Cu–Ag metallic glass coating with ≈95% antifouling properties. First, a range of different chemical compositions were prepared via Physical Vapor Deposition magnetron by co-sputtering Zr, Cu, and Ag onto a Polybutylene terephthalate (PBT) substrate among which Zr93·5 Cu6·2 Ag0.2, Zr76·7 Cu22·7 Ag0.5, and Zr69·3 Cu30·1 Ag0.6 were selected to be further investigate for their surface properties, antibacterial activity, and cytocompatibility. Scanning electron microscopy (SEM) images revealed a micro-roughness fibrous structure holding superhydrophobic properties demonstrated by specimens' static and dynamic contact angle measurements ranging from 130° to 150°. The dynamic contact angle measurements have shown hysteresis below 10° for all coated samples which indicated the superhydrophobicity of the samples. To distinguish between antifouling and bactericidal effect of the coating, ions release from coatings into Luria Bertani Broth (LB), and Dulbecco's Modified Eagle Medium (DMEM) solutions were evaluated by inductively coupled plasma mass spectrometry (ICP-MS) measurements after 24 ​h and 5 days. Antifouling properties were evaluated by infecting the specimens' surface with the Gram-positive Staphylococcus aureus and the Gram-negative Escherichia coli strain reporting a ≈95% reduction of bacteria adhesion as visually confirmed by FESEM and fluorescent live/dead staining. Human mesenchymal stem cells (hMSC) were used for direct cytocompatibility evaluation of coated samples and their metabolic activity was evaluated via relative fluorescence unit after 24 ​h and 5 days confirming that it was comparable to the controls (>97% viable cells). The results were further visualized by FESEM, fluorescent staining by Live/Dead Viability/Cytotoxicity Kit and confirmed the cytocompatibility of all coated samples. Finally, hMSC′ cytoplasm was stained by May Grunwald and Giemsa after 5days to detect and visualize the released ions which have diffused through the cells' membrane. Graphical abstract: Image 1